High resolution infrared spectroscopy and global vibrational analysis for the CH3D and CHD3 isotopomers of methane; Molecular Physics; Vol. 108, iss. 7-9 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Bekhtereva E. S. Elena Sergeevna; Albert S.; Bauerecker Z. (S.) H. Zigurd (Sigurd) Hermann; Hollenstein H.; Quack M. (2010, 2010)
Title screen